Identification and significance of Weissella species infections - Kamboj, Kamal; Vasquez, Amber; Balada-Llasat, Joan-Miquel (Frontiers in Microbiology, 2015)
Weissella spp. are non-spore forming, catalase-negative, gram-positive coccobacilli. They are often misidentified by traditional and commercial phenotypic identification methods as Lactobacillus spp. or Lactobacillus-like organisms. Weissella spp. were previously grouped along with Lactobacillus spp., Leuconostoc spp, and Pediococcus spp. Utilization of more sensitive methods like DNA sequencing or Matrix-Assisted Laser Desorption/Ionization Time of Flight Mass Spectrometry (MALDI-TOF MS) has facilitated identification of Weissella spp. as a unique genus. Nineteen species have been identified to date. W. confusa, W. cibaria, and W. viridescens are the only species isolated from humans. The true prevalence of Weissella spp. continues to be probably underestimated. Weissella spp. strains have been isolated from a wide range of habitats including raw milk, feces, fermented cereals, and vegetables. Weisella is believed to be a rare cause of usually nonfatal infections in humans, and is often considered a contaminant. However in recent years, Weissella spp. have been implicated in bacteremia, abscesses, prosthetic joint infections, and infective endocarditis. Alterations of the gut flora from surgery or chemotherapy are believed to facilitate translocation of Weissella spp. due to disruption of the mucosal barrier, predisposing the host to infection with this organism. Implications of the isolation of Weissella spp. from blood must be interpreted in context of underlying risk factors. Weissella spp. are inherently resistant to vancomycin. Therefore, early consideraton of the pathogenic role of this bacteria and choice of alternate therapy is important to assure better outcomes.